PEMETAAN SISTEMATIS STRATEGI KEUNGGULAN BERSAING INDUSTRI KELAPA SAWIT DI PROVINSI RIAU - Lie Othman; Mashur Fadli (JIP ( Jurnal Industri dan Perkotaan ), 2020)
This research is an explanation regarding the systematic mapping of the Oil Palm Industri Business Strategy in Riau Province. Oil palm as a commodity of plantation products has an important role in economic activity inIndonesia. Apart from being one of the country's foreign exchange earners, palm oil is also labor intensive, so it absorbs a lot of labor. From a comparative point of view, the potential for the Indonesian palm oil commodity hasgood prospects, because Indonesia's climate and weather are suitable for oil palm cultivation. Researchersconducted research in Riau Province considering that Riau Province is a province with the largest oil palm plantation area in Indonesia. This study uses a literature study method that explores the results of previous research and publications with the Systematic Mapping Study method. The results of the study found that the concepts of structure, behavior, performance have not been used by researchers in the oil palm industri.